Proteome-wide mapping of PQS-interacting proteins in Pseudomonas aeruginosa. Issue 8 (30th January 2018) - Dandela, Rambabu; Mantin, Danielle; Cravatt, Benjamin F.; Rayo, Josep; Meijler, Michael M.
Abstract : Development and application of chemical probes to globally map key virulence proteins of pathogenic bacteria. Abstract : The opportunistic human pathogen Pseudomonas aeruginosa secretes 2-heptyl-3-hydroxy-4-quinolone (PQS), a quorum sensing (QS) signal that regulates the expression of numerous virulence genes. Here we report the development and application of chemical probes to globally map quinolone binding proteins. The revealed quinolone interactome contains both known as well as newly identified virulence factors and presents new targets for the treatment of bacterial infections.